Global Pandemic and Its Effect on Papuan EFL Students’ Digital Concepts - Betaubun, Martha; Anggawirya, Arin Mantara (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to reveal the influence of this pandemic on understanding digital concepts owned by native Papuan students who learn English, both indigenous and non-indigenous students. This study is categorized as a survey study. This study surveyed the EFL students’ digital concepts during global pandemic. To attain the data, researchers distributed questionnaires to respondents. The questionnaires were distributed to 228 students in eastern Indonesia. The data analysis technique used in this study is a quantitative descriptive analysis. The results of this study indicate that, in general, the understanding of digital concepts of EFL students in eastern Indonesia is still below the average value. In demographic mapping based on indigenous students and non-indigenous students, there are no significant differences. Even in some aspects, indigenous students in terms of knowledge. Finally, in comparing the duration of playing games as an alternative to relieve stress during the pandemic, those who do not play games tend to have a lower understanding than those who intensely play games for more than 4 hours. The research findings can be a catalyst for future studies digital concept in the realm of learning.